Innate Immune Memory in Hematopoietic Stem/Progenitor Cells: Myeloid-Biased Differentiation and the Role of Interferon - Chen, Lili; Ozato, Keiko (Frontiers in Immunology, 2021)
Innate immune memory was first described for monocytes and other myeloid cells. This memory is designated Immune Training, in which the host animals that had experienced pathogen infection earlier acquire improved resistance to a second infection. Innate immune memory is mediated by an epigenetic mechanism traced to transcriptional memory that is conserved throughout evolution and has been selected for the ability to mount an adaptive response to shifting environments. Accumulating evidence shows that not only peripheral myeloid cells but hematopoietic stem cells (HSCs/HSPCs) to acquire epigenetic memory upon pathogen exposure. Systemic pathogen infection causes HSCs to exit from quiescence and facilitate myeloid-biased differentiation that leads to efficient host defense. This sequence of events is common in HSC memory generation, which is triggered by different stimuli. Recent studies show that not only pathogens but other stimuli such as metabolic stress can generate memory in HSCs. This review summarizes recent publications relevant to HSC memory. We discuss the current understanding of initial sensors, soluble mediators/cytokines involved in memory formation, including Type I and Type II interferons along with future implications.